Nilai Pendidikan Islam pada Upacara Adat Kematian Masyarakat Melayu Landak - Siti Mery Sukarniawati (Institut Agama Islam Negeri Palopo, 2019)
Loss of culture are eroded by the strong influx of progress time progress , causing forget it cultural in this process there are various kinds of values education local knowledge .When exhumated and learned shall be form the character of students who appropriate to the state of social life in the area .The goal is to dig values education local knowledge to be applied for education .Excavated and found with the use of the qualitative method approach ethnography .So successful of values islamic education that is in a ceremony death the community malay village the king kabupaten porcupine , namely value attitude generous , cultivating charity , strengthening our relationship , reading Qur’an Habbit .Zikir , tahlil , attitude gotong royong , empathy , sympathy , and honor guests habbits .Keywords: the value of islamic education , customary death , malay porcupine